The In Situ Polymerization and Characterization of PA6/LiCl Composites - Sun, Dandan; Li, Jiang; Pan, Qinghua; Hao, Chaowei; Lai, Guoqiao (Journal of Spectroscopy, 2013)
PA6/LiCl composites were synthesized by in situ anionic polymerization based on the interaction between the inorganic salts and PA6. Sodium hydroxide as initiator and N-acetylcaprolactam as activator were used in the preparation of PA6/LiCl composites with variety of LiCl content. X-ray diffraction (XRD) and differential scanning calorimeter (DSC) testing results showed that both of degree of crystallinity and melting temperature of the composites were decreased under the influence of LiCl. And the γ crystal phase proportion increased with increasing the LiCl content to appropriate amount.